The Use of Deixis in Students’ Writing of Descriptive Texts - Mutia Olivia Indriastuti; Anni Holila Pulungan; Muhammad Natsir (RIRAI Publisher, 2023)
This study aims to identify the types of deixis, and the deixis used, and to analyze the reason deixis used in the students’ writing descriptive text at the tenth grade MIA 2 high school Kemala Bhayangkari Medan. This research used descriptive qualitative research where the participants were 20 students who took English class. The result of this research showed five types of deixis, how the deixis are used, and the reason deixis is used in their writing using Levinson's theory (1983). Five types of deixis are spatial deixis, temporal deixis, person deixis, social deixis, and discourse deixis. From 20 total data, the researcher found 186 deictic words in the students’ writing. 84 or 45% in the spatial deixis, 40 or 22% in the person deixis, 25 or 13% in the temporal deixis, 22 or 12% in the discourse deixis, and 15 or 8% in the social deixis. Therefore, the reasons students used deixis are: to Indicate a specific location, chronology of events, to convey a personal point of view, to incorporate cultural and social signifiers, and to create a strong and coherent connection.